Lokalitas Tafsir Al-Qur’an Minangkabau (Studi Tafsir Minangkabau Abad ke-20) - Aldomi Putra; Hamdani Anwar; Muhammad Hariyadi (AL QUDS : Jurnal Studi Alquran dan Hadis, 2021)
Locality of Minangkabau in Interpretation of the Qur’an: (the study of Minangkabau interpretation of the 20th century)This study aims to find the absorption of locality in the interpretation of the Qur'an in Minangkabau, and to prove that Anthony H. Johns 'statement "cannot be denied the influence of local language in explaining the Al-Qur'an" and Islah Gusmian's statement "tafsir Al-Qur'an as a cultural product, it certainly struggles with tradition, culture, and socio-political realities”. This research is a qualitative research type of library research (library research), which uses a historical-philosophical approach. The primary sources of this research are the interpretation of Tafsir al-Burhân by Haji Abdul Karim Amarullah, Risâlah al-Qaul al-Bayyân fî Tafsîr al-Qur'ân, the work of Syeikh Sulaiman Arrasuli, and the tafsir of al-Da'wah wa al-Irsyâd ilâ Sabîl al -Rasyad by Abdul Lathif Syakur. This research found several aspects of locality in the interpretation of the Al-Qur'an Minangkabau, namely; first, the writing of interpretation as a request from the community, second, the absorption of local languages in translating and interpreting the Qur'an, third, using local samples in interpretation, fourth, the absorption of local customs in interpretation, and fifth using Minangkabau adagium in interpretation. Thus, the Minangkabau tafsir al-Qur'an is full of locality absorption